Eco-Hotel At The Balige Natural Resort Area - Siregar, Hizkia Sahatasi; Siahaan, Nelson (Talenta Publisher, 2019)
With a tourism development discourse in Lake Toba, North Sumatra, the tourism minister is targeting up to 1 million tourists to visit Lake Toba in 2019. Therefore, it is necessary to develop a stay and relaxation that can support tourist activities in Lake Toba. At the moment there is no housing to stay and relax at the same time at Balige. Therefore, it is necessary to design a house to rest and relax in there. The Resort hotels in the Balige Nature Tourism Area are expected to be a destination for local and foreign tourists. The Resort Hotels in the Balige Nature Tourism Area are using the concept of